PUBLIC COMPLAINT HANDLING SERVICES ABOUT PUBLIC STREET LIGHTING AT THE DINAS KEBERSIHAN RUANG TERBUKA HIJAU SURABAYA CITY - Johan Vivaldi Alex Sander; Ananta Prathama (DIA: Jurnal Administrasi Publik, 2021)
Complaints are an important factor to assist the government in improving the quality of public services. During 2016-2020 in the City Government of Surabaya, the Green Open Space Cleaning Service was ranked as the top 5 Regional Apparatus Organization that received a lot of complaints. The highest complaint was related to public street lighting in the city of Surabaya. The purpose of this study was to determine the service for handling complaints about public street lighting(PJU) at the Dinas Kebersihan Ruang Terbuka Hijau (DKRTH) Surabaya City. This research uses qualitative methods with qualitative data analysis techniques. The results showed that the complaint handling service of the Dinas Kebersihan Ruang Terbuka Hijau (DKRTH) was based on the Peraturan Daerah No. 4 Tahun 2014 Pasal 38 Ayat 2 concerning the Complaint Handling System, namely: 1). In the institutional aspect, there are a series of work rules, allowed and prohibited actions in handling complaints, and information provided to the public. 2). Procedural aspects, response when receiving complaints and follow-up complaints. 3). Integrative, available channels between officers and available media channels for the public. 4). Comprehensive in nature, examines the type and nature of complaints.